Design and fabrication of multilayer inkjet-printed passive components for printed electronics circuit development - Correia, V. (2018)
Printing electronic passive components suffer from the lack of a wide variety of appropriate materials for developing components with specific characteristics, for specific dimensions. This paper introduces a multilayer approach for the inkjet printing of resistors, inductors and capacitors, showing that it is possible to manufacture tailored passive circuit elements and therefore their implementation into functional printed electronics. The materials and process steps for the manufacturing, the individual component characteristics and the equivalent circuit is provided for all passive devices.